Wage Levels and Employment — On Economic Policy Advice Using the Multi-Country Model NiGEM - Thomas Theobald; Rudolf Zwiener; Camille Logeay (Wirtschaftsdienst)
Abstract The restrictions of the NiGEM initial model and their relevance over the last decade and a half have produced oft-cited economic policy advice that can hardly be justified empirically: Wage increases will result in significant employment losses. But with statistically validated modifications, the results and the economic policy statements of the simulations by the German Council of Economic Experts and the Deutsche Bundesbank find that a higher wage path now stimulates domestic demand more strongly because the set employment losses do not materialise. There are no noticeable losses in growth and employment for the German economy.